Gender and dynastic political recruitment - Olle Folke; Johanna Rickne; Daniel M. Smith (Research Institute of Industrial Economics (IFN), 2018)
Throughout history and across countries, women appear more likely than men to enter politics at the heels of a close relative or spouse. We provide a theoretical explanation for this dynastic bias in gender representation that integrates political selection with informational inequalities across social groups. Legislator-level data from twelve democracies and candidate-level data from Ireland and Sweden support the idea that dynastic ties help women overcome a vote disadvantage in elections, and that the quality of predecessors may be more relevant in the recruitment of female successors than their male counterparts. Moreover, the role of informational inequalities in explaining the dynastic bias in gender representation is empirically supported by a declining gap over time, and following the introduction of a gender quota in Sweden.
Keywords: D72; 330; Dynasties; Gender representation; Gender quota; Sweden; Ireland